A Study on Stress Management Strategies in Modern Business - Dr.V.J.R.Emerlson Moses and Dr.S.Binduja (International journal of economic perspectives, 2022)
Everyone experiences stress at some stage in their life. It is a way for us to know that something in our life is causing us concern and is affecting how we are thinking and feeling.Stress is not always bad. In small doses, it can help you perform under pressure and motivate you to do your best, but when you are constantly running in emergency mode, your mind and body pay the price.Stress management is defined as the tools, strategies, or techniques that reduce stress and reduce the negative impacts stress has on your mental or physical well-being. A variety of techniques can be used to manage stress. These include mental, emotional, and behavioral strategies. When stress management is used regularly and in response to stressful life events, we can optimize our well-being.Stress in the workplace is considered to be caused by various things. For example, people are often expected to work extra hard to get positive results. At the same time, their superiors also expect them to be available 24/7 because communication is always available through the internet nowadays. In this study highlight about causes of stress, stress management strategies and importance.